2016
DOI: 10.4258/hir.2016.22.2.142
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Nursing Informatics Education in Korea

Abstract: ObjectivesThis study presents the current status of nursing informatics education, the content covered in nursing informatics courses, the faculty efficacy, and the barriers to and additional supports for teaching nursing informatics in Korea.MethodsA set of questionnaires consisting of an 18-item questionnaire for nursing informatics education, a 6-item questionnaire for faculty efficacy, and 2 open-ended questions for barriers and additional supports were sent to 204 nursing schools via email and the postal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 14 publications
(24 reference statements)
0
17
0
Order By: Relevance
“…The increasingly complex requirements of today’s nursing practitioners have been accompanied by demands on nurse educators to improve the situation to facilitate learning in the clinical area [ 33 ]. The proportion of schools teaching nurses increased from 20.8% in 1999 to 52.8% in 2014 [ 34 ]. However, only a small proportion of nurses in practice have formal nursing education beyond senior high school.…”
Section: Discussionmentioning
confidence: 99%
“…The increasingly complex requirements of today’s nursing practitioners have been accompanied by demands on nurse educators to improve the situation to facilitate learning in the clinical area [ 33 ]. The proportion of schools teaching nurses increased from 20.8% in 1999 to 52.8% in 2014 [ 34 ]. However, only a small proportion of nurses in practice have formal nursing education beyond senior high school.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaires consist of 21 questions and have both structured and open-ended response options. There are 7 demographic questions for teacher: age, country and city, current position, education-level, educational background, teaching year, and subject type [6][7][8][9][10]. The 11 questions are on the ERL in nursing education, all used Likert 5point scale from 'not much' to 'very much'.…”
Section: Questionnaire Designmentioning
confidence: 99%
“…NI education has been found to reduce medication errors and improve productivity and enhance coordination among nurses and the rest of the multidisciplinary healthcare team [14]. A study conducted in 2016 in South Korea by Jeon et al [2] reviewed the status of NI education and found that 55.3% of nursing schools had introduced an informatics course within the previous 5 years; these courses were introduced as electives rather than as mandatory courses. A survey conducted on NI education in 1999 in Korea by Park et al [15] found that curricula varied between nursing schools, with content consisting of computer basics, concepts and elements of NI, and NI utilization in practice, education, research, and administration.…”
Section: Introductionmentioning
confidence: 99%
“…As part of the 21st-century scientific transformation, nursing informatics (NI) has improved the quality, safety, and effectiveness of healthcare [ 1 , 2 ]. NI has accelerated the computerization of human healthcare tasks, in particular the transition of paper nursing records to electronic Medical Records [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%